2016
DOI: 10.3389/fneur.2016.00125
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of Truncal Ataxia and HINTS as Cardinal Signs for Acute Vestibular Syndrome

Abstract: The head impulse, nystagmus type, test of skew (HINTS) protocol set a new paradigm to differentiate peripheral vestibular disease from stroke in patients with acute vestibular syndrome (AVS). The relationship between degree of truncal ataxia and stroke has not been systematically studied in patients with AVS. We studied a group of 114 patients who were admitted to a General Hospital due to AVS, 72 of them with vestibular neuritis (based on positive head impulse, abnormal caloric tests, and negative MRI) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
3
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(133 citation statements)
references
References 24 publications
5
113
3
12
Order By: Relevance
“…Ideally, have the patient walk unassisted, but for severely nauseated patients too symptomatic to walk, test for truncal ataxia by asking the patient to sit upright in the stretcher with arms crossed. Patients who cannot walk or sit up unassisted are unsafe for discharge and are more likely to have a stroke (or other CNS pathology) rather than vestibular neuritis (27,44,77). Although American emergency physicians are uncomfortable using HINTS testing and instead overuse CT, one study reported that specially trained emergency physicians using these bedside examination elements decreased both CT use and hospitalization (62,63,78).…”
Section: A New Diagnostic Paradigmmentioning
confidence: 99%
“…Ideally, have the patient walk unassisted, but for severely nauseated patients too symptomatic to walk, test for truncal ataxia by asking the patient to sit upright in the stretcher with arms crossed. Patients who cannot walk or sit up unassisted are unsafe for discharge and are more likely to have a stroke (or other CNS pathology) rather than vestibular neuritis (27,44,77). Although American emergency physicians are uncomfortable using HINTS testing and instead overuse CT, one study reported that specially trained emergency physicians using these bedside examination elements decreased both CT use and hospitalization (62,63,78).…”
Section: A New Diagnostic Paradigmmentioning
confidence: 99%
“…In another study of AVS presentations, all of the stroke patients (42/42) had either central nystagmus or severe imbalance defined as inability to walk without support. 42 The head impulse test and test of skew deviation can also inform the likelihood of stroke. In a singlecenter study with two neuro-ophthalmologists performing the bedside examination, the HINTS examination alone had a sensitivity of 97% (109/113: 95% CI, 92-99%) and specificity of 84% (65/77: 95% CI, 75-91%).…”
Section: Approach To the Acute Vestibular Syndrome Presentationmentioning
confidence: 99%
“…Patients who cannot walk or sit up unassisted are more likely to have a stroke (or other CNS pathology) rather than vestibular neuritis. 9,32,75 The use of tandem gait testing helps evaluate for midline cerebellar function, but may be impaired in older individuals, or in patients with peripheral causes of dizziness.…”
Section: Acute Vestibular Syndromementioning
confidence: 99%